Mechanical Characterization and Dynamic Mechanical Analysis of Recycled Low Density Polyethylene Filled Unsaturated Polyester Composite - Adegboro, Narcillina Nkechi; Isa, Muhammed Tijjani; Bello, Tajudeen Kolawole (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Unsaturated polyester resin (UPR) is widely used as matrix in composite development; however, it has poor toughness property. To solve this problem, many researchers have used different tougheners to modify the resin, but the use of recycled low-density polyethylene (RLDPE) has not been explored. This work is aimed at modifying unsaturated polyester resin (UPR) with recycled low-density polyethylene (RLDPE) as a toughener and establishing the effects on the mechanical and dynamic mechanical performance of the RLDPE-filled polyester composite. Unsaturated polyester resin was modified with 1.18 mm RLDPE at different proportions of 1-4 wt%. Casting method was used for the production and the mechanical and dynamic mechanical analyses of the produced composite materials were carried out using ASTM standards. UPR modified with 1.5 wt% RLDPE exhibited the best impact than the un-modified UPR. The control (un-modified) sample had the highest flexural and tensile strength of 18 MPa and 14.02 MPa respectively which was about 26% and 25% higher than UPR modified with 1 wt% RLDPE. The Dynamic Mechanical Analysis (DMA) result showed that the composite does not depend strongly on the modifier loading as no regular pattern was observed for storage modulus, loss modulus and damping factor respectively.